KAJIAN ILMU FALAK PERBEDAAN PENENTUAN AWAL BULAN KAMARIAH: Antara Khilafiah Dan Sains - Jayusman Jayusman (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
Abstract There are distinctions between Islamic astronomers in Indonesia on how to determine the beginning of kamariah. Some of them prefer using rukyatul hilal while some others tend to employ hisab. The disparities emerge because the Islamic astronomers have different understanding of shar’i argumentation and its application. The development of Islamic astronomy in determining the beginning of kamariah is not in line with the development of science. For instance, there are some Islamic astronomers who still make use of traditional method even though the result is not accurate. This article is not aimed at integrating the method of hisab and rukyat but to explain the construct/form of disparity in determining the beginning of kamariah. This article also conveys the view of syar’i especially Islamic astronomy in dealing with the differences.